Effects of Ethyl Pyruvate on Bile Duct Ligation-Induced Liver Fibrosis by Regulating Nrf2 Pathway and Proinflammatory Cytokines in Rats. (20th December 2019) - Zong, Yonghua; Zhang, Mingxiao; Li, Shuai; Qi, Wenqian; Li, Juan; Liu, Tonghua; Yang, Huijun; Lu, Chen; Hu, Xiaosong
Abstract : Aim . The aim of this paper is to investigate the effects of ethyl pyruvate (EP) on experimental liver fibrosis induced by bile duct ligation (BDL) and explore the underlying molecular mechanisms. Material and Method . Rats were randomly divided into three groups: the sham group, the BDL group, and the BDL+EP group. Liver fibrosis was induced by common bile duct ligation and was evaluated by serum biochemical parameter levels, Masson's trichrome staining, α -SMA expression, and collagen I deposition. The levels of Nrf2 signaling pathway-related antioxidant genes (Nrf2, SOD2, NQO1, and GSH-Px) in liver tissues were also measured. Meanwhile, the mRNA expression levels of HMGB1, IL-1 β, TNF- α, and HSP27 were analyzed. In BDL-induced liver fibrosis rats, the successfully established model was confirmed by the significant increase of serum ALT and AST levels, the high liver fibrosis score, α -SMA expression, and collagen deposition. Results . Compared with the BDL group, EP administration could diminish fibrosis level and substantially increase the expression of Nrf2 signaling pathway-related antioxidant genes. Furthermore, EP significantly suppressed the mRNA expression levels of HMGB1, IL-1 β, TNF- α, and HSP27. Conclusions . The results suggested that EP administration could effectively inhibit the liver fibrosis induced by BDL in rat, which may be associated with the enhanced activity of Nrf2 to mediate antioxidant enzyme system and downregulate the inflammatory genes.